Effect of Photoperiod on the Production of Chukar Partridges (Alectoris chukar) - Alva, V.I.A.; Quintana , L.J.A.; Gonzales-Rebeles, I.C.; Gonzalez, A.M. (International Journal of Poultry Science, 2015)
This study evaluated the effect of variations in photoperiod duration on production indicators such as amount of eggs-laid and weight in chukar partridges (Alectoris chukar). Ninety individuals were divided into groups of 3 males and 7 females per cage (9 cages). Three different photoperiod treatments were used (18, 16 and 14 h light) with three repetitions per treatment. Males and females were randomly selected for each group. Means between treatments were compared using ANDEVA with Tukey’s multiple comparisons in a GLM using the SAS V.8.0 software package. The following variables were evaluated during 18 production weeks: egg weight (EW), egg mass (EM), eggs per female (EF) and laying percentage (LP). Significant differences (p<0.05) were found in EW between 18 and 14 h light, representing a 7.1% in EW with decreasing photoperiod. No significant differences (p>0.05) were found in the remaining parameters between treatments. There was an improvement of all production variables at the smallest photoperiod (14 h) even though only EW was statistically significant.